(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
The importance of educational values in today’s society.Education plays a crucial role in today’s contemporary society, being of particular importance in the development of individuals and communities. In a constantly changing world, where technology and information are accessible at every step, education becomes a fundamental pillar for the formation of a progressive and sustainable society. This article aims to explore the importance of educational values in today’s society, highlighting its key aspects and its effects on the individual and society as a whole. By analyzing the benefits of education, we will discover that an educated society is a strong one and able to face the challenges of the 21st century. Education plays an extremely important role in the development of contemporary society, having a significant influence on the formation and shaping of the individual. Through education, people acquire knowledge, skills and competences that help them develop and integrate effectively into society. In addition, education contributes to the formation of individual and collective values, attitudes and behaviours. A quality education is essential for a healthy and progressive society. It provides equal opportunities for all citizens, regardless of origin or social status. Through education, equal opportunities are promoted and discrimination and social exclusion are fought. Also, through the educational system, young people are trained to become responsible citizens, able to contribute to the development of their society in a constructive way. Through education, people learn to think critically and make informed decisions, develop their creativity and communication skills. Education also helps them develop their emotional intelligence and manage their emotions effectively. These skills are essential in contemporary society, which faces increasingly complex and diverse challenges.